Baseline anemia and its impact on midterm outcome after transcatheter aortic valve implantation. Issue 1 (3rd May 2016) - Seiffert, Moritz; Conradi, Lenard; Gutwein, Andreas; Schön, Gerhard; Deuschl, Florian; Schofer, Niklas; Becker, Nina; Schirmer, Johannes; Reichenspurner, Hermann; Blankenberg, Stefan; Treede, Hendrik; Schäfer, Ulrich
Abstract : Background: Anemia is linked to impaired outcome in patients with cardiovascular diseases. We sought to characterize the impact of baseline anemia on mid‐term outcome after transcatheter aortic valve implantation (TAVI). Methods and results: Data of 1201 consecutive TAVI patients were retrospectively analyzed. Baseline anemia was defined according to the WHO (hemoglobin <12g/dl [female], <13g/dl [male]). It was prevalent in 59.0% of patients and associated with a higher preoperative risk (STS‐PROM 7.8 ± 5.7 vs. 6.2 ± 4.1%, P  < 0.001). Survival was similar at 30 days (90.5 vs. 91.2%, P  = 0.626) but NYHA functional capacity was impaired in patients with baseline anemia (classes III/IV: 20.6 vs. 15.6%, P  = 0.006). Low baseline hemoglobin (OR 0.85, CI 0.73–0.98, P  = 0.025), blood transfusion (OR 2.42, CI 1.38–4.28, P  = 0.002), and bleeding complications (OR 2.21, CI 1.27‐3.81, P  = 0.005) were in addition associated with acute kidney injury after TAVI. Three‐year survival was reduced (49.6 vs. 64.9%, P  = 0.002) and baseline anemia was linked to increased mid‐term mortality (HR 1.43, CI 1.13–1.82, P  = 0.003), however its effect was surpassed by the adverse impact of periprocedural complications. Conclusions : Baseline anemia was associated with increased morbidity and mortality after TAVI. Preprocedural hemoglobin levels need to be assessed for risk stratification and blood conservation management seems essential. As a potentially modifiable target, the role of pretreatment of anemia prior to TAVI remains to be determined. © 2016 Wiley Periodicals, Inc.